The Influence of CEO Narcissism on Financial Performance with Corporate Social Responsibility (CSR) as a Mediating Variable - Ita Fionita; Nyoman Tika Lestari; Khilma Safira Situmorang; Lala Nurbaiti; Arica Cindy Listya; Noval Dewa Brilian; Sinta Adelia (Prosiding International conference on Information Technology and Business (ICITB), 2022)
In Indonesia, one of the state-owned companies, namely Garuda Indonesia, manipulated the financial statements in 2018. The case began with the results of Garuda Indonesia’s financial statements for the 2018 financial year, which posted a net profit of USD 809.85 thousand, or Rp. 11.33 billion (assuming an exchange rate of Rp. 14,000 per US dollar). There was an error in recording receivables that had not been received but had been recorded as income by PT. Mahata Aero Teknologi related to wi-fi on board installation. Financial statement fraud was due to the President Director (CEO) of PT Garuda Indonesia controlling all its employees to act according to their wishes. This study aims to determine the influence of CEO narcissism on financial performance mediated by corporate social responsibility (CSR). The type of research used was quantitative research using causal associative methods. The sampling technique used was purposive sampling, namely selecting samples with certain criteria and producing as many as 17 observations of state-owned companies in 2018–2021. Data analysis in this study used multiple linear regression analysis. Keywords— CEO Narcissism, Financial Performance, Corporate Social Responsibility (CSR)